Magnetic Resonance Imaging During a Pandemic: Recommendations by the ISMRM Safety Committee. Issue 5 (20th December 2021) - Collins, Jeremy D.; Rowley, Howard; Leiner, Tim; Reeder, Scott; Hood, Maureen; Dekkers, Ilona; Tha, Khin; Gulani, Vikas; Kopanoglu, Emre; ,
Abstract : The COVID‐19 pandemic highlighted the challenges delivering face‐to‐face patient care across healthcare systems. In particular the COVID‐19 pandemic challenged the imaging community to provide timely access to essential diagnostic imaging modalities while ensuring appropriate safeguards were in place for both patients and personnel. With increasing vaccine availability and greater prevalence of vaccination in communities worldwide we are finally emerging on the other side of the COVID‐19 pandemic. As we learned from our institutional and healthcare system responses to the pandemic, maintaining timely access to MR imaging is essential. Radiologists and other imaging providers partnered with their referring providers to ensure that timely access to advanced MR imaging was maintained. On behalf of the International Magnetic Resonance in Medicine (ISMRM) Safety Committee, this white paper is intended to serve as a guide for radiology departments, imaging centers, and other imaging specialists who perform MR imaging to refer to as we prepare for the next pandemic. Lessons learned including strategies to triage and prioritize MR imaging research during a pandemic are discussed. Level of Evidence: 5 Technical Efficacy: Stage 5